2013
DOI: 10.1055/s-0033-1339199
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Suzuki-Miyaura Coupling Reaction of Arylpropar­gylic Bromides with Aryl- and Alkenylboronic Acids

Abstract: In the absence of transition-metal catalyst, Suzuki-Miyaura coupling reaction between aryl-and alkenylboronic acids and arylpropargylic bromides proceeded to give the corresponding acetylenic products selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Quaternary ammonium salt derivatives of di-t-butylphosphines such as 133 and 134 are designed for reactions of chloroarenes in aqueous acetonitrile [184]. The glycosides of arylphosphines 135 [185], 136 [186], 137 [187], and 138 [188] are a new class of ligands used for two-phase or single-water-phase catalysis. Their relative efficiency for oxidative addition is in the order of the electron-donating ability of phosphine ligands to the palladium metal center (138 i 135 Z 137 i TPPMS i TPPTS).…”
Section: [138] and 2-(di-t-butylphosphino)biphenyl (105c) [135] And Qmentioning
confidence: 99%
“…Quaternary ammonium salt derivatives of di-t-butylphosphines such as 133 and 134 are designed for reactions of chloroarenes in aqueous acetonitrile [184]. The glycosides of arylphosphines 135 [185], 136 [186], 137 [187], and 138 [188] are a new class of ligands used for two-phase or single-water-phase catalysis. Their relative efficiency for oxidative addition is in the order of the electron-donating ability of phosphine ligands to the palladium metal center (138 i 135 Z 137 i TPPMS i TPPTS).…”
Section: [138] and 2-(di-t-butylphosphino)biphenyl (105c) [135] And Qmentioning
confidence: 99%
“…In 2013, we reported the transition-metal-free cross-coupling reaction of alkenylboronic acids and arylboronic acids with propargylic bromides in the presence of Cs 2 CO 3 as a base [Scheme 1 (b)]. [5,6] Recently, Gandon and co-workers found that the cross-coupling reaction of propargylic alcohols with alkenylboronic acids proceeds efficiently by using Ca(NTf 2 ) 2 as a catalyst [Scheme 1 (c)]. [7][8][9] Herein, we report that the cross-coupling reaction of propargylic acetates with alkenylboronic acids proceeds spontaneously to give 1,4-enynes in good yields [Scheme 1 (d)].…”
Section: Introductionmentioning
confidence: 99%
“…In this reaction, a stoichiometric amount of n BuLi is used as a base to prepare (halovinyl)(propargyloxy)boron halides working as a key intermediate. In 2013, we reported the transition‐metal‐free cross‐coupling reaction of alkenylboronic acids and arylboronic acids with propargylic bromides in the presence of Cs 2 CO 3 as a base [Scheme (b)] , . Recently, Gandon and co‐workers found that the cross‐coupling reaction of propargylic alcohols with alkenylboronic acids proceeds efficiently by using Ca(NTf 2 ) 2 as a catalyst [Scheme (c)] .…”
Section: Introductionmentioning
confidence: 99%
“…Water is an inexpensive, readily available, non‐toxic and environmentally friendly alternative solvent in organic synthesis but is especially important in facilitating catalyst–product separation. Casalnuovo and co‐workers developed the Suzuki reaction in aqueous solvents catalyzed by TPPMS/Pd(OAc) 2 (TPPMS = PPh 2 ( m ‐C 6 H 4 SO 3 K), while several water‐soluble phosphine analogues have also been developed . Buchwald's group synthesized a very effective sulfonated phosphine ligand for Suzuki reactions in aqueous media .…”
Section: Introductionmentioning
confidence: 99%